FENOMENA PERTUNJUKAN ORGEN TUNGGAL: STUDI KASUS ARTIS PENDUKUNG NAGARI TIKU KABUPATEN AGAM PROVINSI SUMATERA BARAT - Juli Boru Nauli; Adriana Gusti; Ninon Syofia (Garak Jo Garik : Jurnal Pengkajian dan Penciptaan Seni, 2023)
This paper discusses the Commercialization of Single Orgen Performances: A Case Study of Supporting Artists in Nagari Tiku, Agam Regency, West Sumatra Province. This paper is a qualitative research with descriptive analysis method, which describes and describes according to the data obtained in the field according to the phenomenon that actually happened then this data was analyzed. The theory used in this research is the commercialization of single organ performances: the case study on this artist is the economic theory proposed by Muhammad Dinar and Muhammad Hasan and the performance theory proposed by Sal Murgiyanto. In addition, the supporting theory is the sociological theory proposed by J. Dwi Narwoko-Bagong Suyanto ed, and the theory of Potts. The results of the discussion obtained in the study are, The swaying performances of supporting artists in the single organ on Tang Bungkuih Night were originally intended as entertainment, but now there are performances by the supporting artists of the single organ as an arena to seek profit with a high selling price, so they sacrifice their self-esteem. as women to meet economic needs. On the one hand, there was a shift in the values of Religion, Customs, and Education during the single organ show at Malam Tang Bungkuih..